2011
DOI: 10.1159/000326763
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Linkage Scan for Diabetic Renal Failure and Albuminuria: The FIND Study

Abstract: Background: Diabetic nephropathy (DN) is a leading cause of mortality and morbidity in patients with type 1 and type 2 diabetes. The multicenter FIND consortium aims to identify genes for DN and its associated quantitative traits, e.g. the urine albumin:creatinine ratio (ACR). Herein, the results of whole-genome linkage analysis and a sparse association scan for ACR and a dichotomous DN phenotype are reported in diabetic individuals. Methods: A genomewide scan comprising more than 5,500 autosomal single nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 53 publications
3
28
0
Order By: Relevance
“…After fine-mapping the region around the 22q11 locus the best linkage signal was detected at 3 cM (D22S420) and this locus does not overlap with any previously reported DN locus detected in patients with T1D. On the other hand, a locus approximately 20 Mb apart from our susceptibility region has in the FIND Study recently been linked to urinary albumin∶creatinine ratio in Mexican-Americans with diabetes [31]. This region contains the MYH9 (myosin, heavy polypeptide 9, non-muscle) and APOL1 (Apolipoprotein L1) genes associated in African-Americans with diabetic or nondiabetic nephropathy [32][34].…”
Section: Discussionsupporting
confidence: 47%
“…After fine-mapping the region around the 22q11 locus the best linkage signal was detected at 3 cM (D22S420) and this locus does not overlap with any previously reported DN locus detected in patients with T1D. On the other hand, a locus approximately 20 Mb apart from our susceptibility region has in the FIND Study recently been linked to urinary albumin∶creatinine ratio in Mexican-Americans with diabetes [31]. This region contains the MYH9 (myosin, heavy polypeptide 9, non-muscle) and APOL1 (Apolipoprotein L1) genes associated in African-Americans with diabetic or nondiabetic nephropathy [32][34].…”
Section: Discussionsupporting
confidence: 47%
“…A finer mapping of genes susceptible for T2DN in AAs by a GWAS from the same group also revealed the association of MHY9/APOL1 locus [19]. The MYH9 / APOL1 locus was also linked to T2DN in a family linkage study [20]. The function of MYH9/APOL1 in DN is rapidly evolving and remains a hot topic of debate.…”
Section: Geneticsmentioning
confidence: 99%
“…However, linkage scan only in MA participants failed to identify a genetic region significantly linked to DN. Subsequently, Igo et al, [20] performed a genome-wide linkage scan for DN susceptibility loci in the FIND study using the genotypic data of 5,500 SNPs (Illumina panel IV) on 1623 subjects from 1,235 nuclear and extended pedigrees that included 632 subjects from 478 pedigrees of MA participants. DN trait was adjusted for sex.…”
Section: Genome-wide Linkage Scan For Dn In Mamentioning
confidence: 99%
“…However, linkage analysis failed to identify a chromosomal region significantly linked to ACR only in MA participants examined. Subsequently, using the genotypic data of 5,500 SNPs and the ACR data of 1316 MA participants of the FIND study, Igo et al, [20] identified a suggestive evidence for linkage of ACR with a LOD score of 2.29 (P = 0.00058) occurring on chromosome 22q12 near the nonmuscle myosin heavy chain 9 ( MYH9) / apolipoprotein L1 (APOL1) gene region. Age and sex were used as covariates.…”
Section: Genome-wide Linkage Scan For Albuminuria In Mamentioning
confidence: 99%